Nicotiana attenuata α-DIOXYGENASE1 through its production of 2-hydroxylinolenic acid is required for intact plant defense expression against attack from Manduca sexta larvae - Gaquerel, Emmanuel; Steppuhn, Anke; Baldwin, Ian T. (The new phytologist, 2012)
Nicotiana attenuata α-DIOXYGENASE1 (α-DOX1) is an oxylipin-forming gene elicited during herbivory by fatty acid amino acid conjugates (FACs) contained in oral secretions of Manduca sexta.* To understand the roles of Naα-DOX1 and its major product, 2-hydroxylinolenic acid (2-hydroxylinolenic acid), in N. attenuata's anti-herbivore defenses, we used a transgenic line specifically silenced in Naα-DOX1 expression (ir-α-dox1) and monitored 2-HOT production in M. sexta-damaged tissues and its role in influencing the production of direct defense compounds and resistance to this insect.* Attack by M. sexta larvae amplified 2-HOT formation at the feeding sites; a reaction probably facilitated by Naα-DOX1's high pH optimum which allows 2-HOT formation to occur in the more alkaline conditions at the feeding sites or potentially in the insect mouth parts after the leaf tissue is ingested. Manduca sexta larvae performed better on ir-α-dox1 plants than on wild-type (WT) plants as a result of attenuated herbivory-specific JA and 2-HOT bursts as well as JA-inducible well-established defenses (nicotine, caffeoylputrescine and trypsin proteinase inhibitors). Repeated applications of 2-HOT to wounds before insect feeding partly amplified JA-controlled defenses and restored the resistance of ir-α-dox1 plants.* We conclude that 2-HOT, produced by attack-activated α-DOX1 activity, participates in defense activation during insect feeding.